Exosome laden oxygen releasing antioxidant and antibacterial cryogel wound dressing OxOBand alleviate diabetic and infectious wound healing - Shiekh, Parvaiz A.; Singh, Anamika; Kumar, Ashok (Biomaterials, 2020)
Lack of oxygen, reduced vascularization, elevated oxidative stress, and infection are critical clinical hallmarks of non-healing chronic diabetic wounds. Therefore, delivering oxygen, inducing angiogenesis, and management of oxidative stress and infection may provide newer and improved therapeutic avenues for better clinical outcomes in diabetic wound healing. Here, we report the development and evaluation of an exosome laden oxygen releasing antioxidant wound dressing OxOBand to promote wound closure and skin regeneration in diabetic wounds. OxOBand is composed of antioxidant polyurethane (PUAO), as highly porous cryogels with sustained oxygen releasing properties and supplemented with adipose-derived stem cells (ADSCs) exosomes. Exosomes engulfed by the cells enhanced the migration of human keratinocytes and fibroblasts and increased the survival of human neuroblastoma cells under hyperglycemic conditions. OxOBand facilitated faster wound closure, enhanced collagen deposition, faster re-epithelialization, increased neo-vascularization, and decreased oxidative stress within two weeks as compared to untreated diabetic control wounds. The dressing promoted the development of mature epithelial structures with hair follicles and epidermal morphology similar to that of healthy skin. In clinically challenging infected diabetic wounds, these dressings prevented infection and ulceration, improved wound healing with increased collagen deposition, and re-epithelialization. Altogether, OxOBand is a remarkably newer treatment strategy for enhanced diabetic wound healing and may lead to novel therapeutic interventions for the treatment of diabetic ulcers.